Keselarasan Matra dengan Tema Puisi Arab Klasik dalam Puisi-Puisi Umru al-Qais - Minatur Rokhim (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2009)
Umru al-Qais was figure, even an icon in arabic literature in the Pre-Islamic Era (Jahiliyah) be sides al-Nabighah al-Dzubyani, Zuhair ibn Abu Sulma. Antarah ibn Saddad, and others. His compilation of poems wich is written in Diwan Umru al-Qais comprises of 3 Qasidah : the first Qasidah has 91 verses with the total of 221 verses. the theme wich is brought forward by Umru al-Qais in his Diwan are al-risa (elegy or sadness), al-ghazl (romance), al wasf (description) and al-hikmah (advice). THe themes used the rythm of bahr tawil as the bahr character is accurate and appropriate in revealing